Técnicas para mejorar la comprensión lectora: diagramas conceptuales - Torres Tuesta, Rafael Simon (2020)
This research is entitled: Techniques to improve reading comprehension: conceptual_x000D_ diagrams, born just after making a conscious analysis of the various problems of Reading comprehension in Secondary Education students in the year 2019, a year greatly influenced by Great technological advances, media and interaction with various social networks. As a result, it is proposed to improve reading comprehension through the use of conceptual maps, which allow establishing relationships between concepts, ordering and ranking them.After conducting the class on the diagrams or concept maps, an improvement in the Reading comprehension of texts could be evidenced